2020
DOI: 10.21608/jappmu.2020.161189
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Trimming Waste of Mandarin Trees as Feed for Small Ruminants: 3. Evaluation of Growth Performance and Carcass Traits for Barki Lambs

Abstract: Thirty weaned Barki lambs with average body weight 27.56±0.57 kg were blocked by weight and randomly distributed into three equal groups to investigate the impact of feeding trimming waste of mandarin trees (TWMT) on productive performance of lambs. The first group of animals was fed with Berseem hay (BH) plus concentrate feed mixture (CFM) without any additives and kept as a control ration (CR). The second group was fed TWMT plus CFM as untreated ration (UR), where, the animals in group three received TWMT pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…This is mainly referred to the higher cost of BH, which was negatively reflected on the total daily feed cost of the control group and led consequently to higher feed cost. Abo Bakr, et al (2020c) reported that economic efficiency is real affected by some other factors, such as cost of feed ingredients, daily dry matter intake, animals weight gains which might be consequently reflected on the net profit returns. Investigating economic efficiency (Table 10) pointed out to insignificant higher total gain in BH group (the control), while the higher cost of PF supplement (0.9 LE) was due to protected fat supplement negatively reflected on average return income.…”
Section: Economic Evaluationmentioning
confidence: 99%
“…This is mainly referred to the higher cost of BH, which was negatively reflected on the total daily feed cost of the control group and led consequently to higher feed cost. Abo Bakr, et al (2020c) reported that economic efficiency is real affected by some other factors, such as cost of feed ingredients, daily dry matter intake, animals weight gains which might be consequently reflected on the net profit returns. Investigating economic efficiency (Table 10) pointed out to insignificant higher total gain in BH group (the control), while the higher cost of PF supplement (0.9 LE) was due to protected fat supplement negatively reflected on average return income.…”
Section: Economic Evaluationmentioning
confidence: 99%